Modulating immunogenicity of factor IX by fusion to an immunoglobulin Fc domain: a study using a hemophilia B mouse model. (2nd March 2017) - Levin, D.; Lagassé, H. A. D.; Burch, E.; Strome, S.; Tan, S.; Jiang, H.; Sauna, Z. E.; Golding, B.
Abstract : Essentials Fc‐fusion increases a therapeutic's half‐life, but FcγR interactions may impact immunogenicity. Species‐specific Fc‐FcγR interactions allow for mechanistic in vivo studies using mouse models. Fc fusion modulates the immune response to factor IX in hemophilia B mice by eliciting Th1 bias. This model could inform future studies of IgE‐associated anaphylaxis in hemophilia B patients. Summary: Background: Fc fusion is a platform technology used to increase the circulating half‐life of protein and peptide therapeutics. However, there are potential immunological consequences with this approach, such as changes in the molecule's immunogenicity as well as possible interactions with a repertoire of Fc receptors (FcR) that can modulate immune responses. Objectives/Methods: Using a mouse hemophilia B (HB) model, we compared the immune responses to infusions of recombinant human factor IX (hFIX) and hFIX fused to mouse IgG2a‐Fc (hFIX‐mFc). The mFc was employed to allow species‐specific Fc–FcγR interactions. Results: Although treatment with hFIX‐mFc altered the early development of anti‐FIX IgG, no significant differences in anti‐FIX antibody titers were observed at the end of the treatment regimen (5 weeks) or upon anamnestic response (5 months). However, treatment with hFIX‐mFc elicited higher FIX‐neutralizing antibody levels and resulted in reduced IgE titers compared with the hFIX‐treated group. Additionally, differences in plasma cytokine levels and in vitro CD4 + T‐cell responses suggest that whereas hFIX treatment triggered a Th2‐biased immune response, hFIX‐mFc treatment induced Th1‐biased CD4 + T cells. We also show that hFIX‐mFc bound to soluble FcγRs and engaged with FcγRs on different cell types, which may impact antigen presentation. Conclusions: These studies provide a model system to study how Fc‐fusion proteins may affect immune mechanisms. We used this model to demonstrate a plausible mechanism by which Fc fusion may modulate the IgE response to hFIX. This model may be appropriate for investigating the rare but severe IgE‐mediated anaphylaxis reaction to hFIX infusions in HB patients.